The contemporary poetry archive : essays and interventions - Anderson, Linda R., 1950-; Byers, Mark, 1988-; Warner, Ahren, 1986- (Edinburgh University Press, 2019)
These 13 newly commissioned chapters examine the impact of archival poetry collections on both literary scholarship and poetic practice. They examine what we can learn from the drafts, notebooks and personal libraries left behind by poets and look at the ways in which the growth of poetry archives has changed the way poets think about their work. The contributing poets and scholars - including Susan Howe, Sean O'Brien and George Szirtes - present an in-depth account of the significance of poetry archives for contemporary literature. The collection provides a new cross-disciplinary agenda for thinking about the archive as both a source for scholarship and inspiration for creative practice.